Representation of Proverbs in Flemish Marginal Art of the 13th–15th Centuries - Heiremans, Alina (Actual Problems of Theory and History of Art, 2021)
In the article, the author attempts to draw a link between marginal imagery found in Flemish illuminated manuscripts and medieval Flemish and French proverbs, proving that marginalia and folklore have many points of intersection. A common motif, found in the margins of Flemish manuscripts, shows a man and a woman (or two women) fighting for the britches and most likely refers to the proverb “Whoever wins the britches gets the man”. The proverb is also related to two 13th-century fabliaux, where a competition between wife and husband for the man’s britches is emphasized. Many of the marginal images are associated with nudity and, more specifically, with the lower stratum of the body. A common inhabitant of the marginal realm is a nude, or a half-nude man pointing to his buttocks or often plugging his arse with a finger, which might allude to common sayings that circulated in France and Flanders at the time. Some images would refer to the saying “It’s as true as the fact that an arse can sing” (“Il est vrai tout ainsi comme le cul chante”) and others, celebrating the “musical gift” of the arse. The musical butt is frequently encountered in the margins of Flemish manuscripts, and a bagpipe or trumpet appears to be its favourite instrument, as farting would often be compared to trumping in many sayings. A Flemish expression “He shits on the whole world” (“Hij beschijt de geheele wereld”), which became best known through Brueghel’s painting “Netherlandish proverbs”, is reflected in a marginal image of a man, defecating on a globe, is found in the 15th-century book of hours of Roland de Wedergate (MS 158). A Flemish saying “He shits eggs without shells” (“Hij schijt eieren zonder schalen”) might have inspired the recurring image of a man, sitting on the nest full of eggs.